RECOMMENDED BITUMEN EMULSION FOR ROAD CONSTRUCTION: ENHANCING DURABILITY AND SUSTAINABILITY - Nosir Sharibaev; Nurbek Sharibaev; Sherzod Djuraev; Sobir Sharipbaev (European Science Publishing, 2023)
Bitumen emulsion is a versatile binder used in road construction due to its numerous advantages, including improved workability, reduced energy consumption, and enhanced pavement performance. Selecting the right bitumen emulsion for road construction is crucial to ensure long-lasting and sustainable road infrastructure. This article provides an overview of the recommended bitumen emulsion types, their properties, and their application in road construction. It also highlights the benefits of using bitumen emulsion and discusses the factors to consider when choosing the appropriate emulsion for different road construction scenarios. By understanding the recommended bitumen emulsion options, road engineers and construction professionals can make informed decisions to optimize road performance, durability, and sustainability.
Keywords: bitumen emulsion, road construction, binder, workability, energy consumption, pavement performance, properties, application, long-lasting, sustainable.